Comparison of Ignition Control Techniques in HCCI Engines from Theoretical and Practical Perspectives - Yang Jiaqi (E3S Web of Conferences)
Homogeneous Charge Compression Ignition (HCCI) is a cutting-edge combustion engine technology that merges the benefits of both diesel and gasoline engines. In HCCI engines, a uniform mixture of fuel and air enters the combustion chamber during the intake phase, which significantly lowers the average temperature within the chamber. This temperature reduction is crucial as it minimizes the formation of nitrogen oxides (NOx), pollutants that typically form at high temperatures, thus making HCCI engines more environmentally friendly. HCCI engines employ compression ignition, offering greater thermal efficiency than spark ignition engines, which are limited by the potential for knocking. These features make HCCI a promising technology for sustainable development. However, one of the main challenges preventing widespread adoption is the difficulty in precisely controlling the ignition timing. This paper aims to delve into the theoretical and practical aspects of ignition control methods in HCCI engines, highlighting the differences and challenges between theoretical models and real-world applications.